The influence of media representations on citizens' perceptions towards nurses: a comparison between before and after the COVID-19 pandemic - Foà, Chiara; Bertuol, Maria; Baronchelli, Elisa; Beltrami, Giulia; Toninelli, Sara; Zamboni, Luca; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: In December 2019 in Wuhan, China, an outbreak related to a new Coronavirus (Covid-19) rapidly spread to other countries, including Italy, emerged. On 11 March 2020, the WHO declared a state of pandemic. During the ensuing health crisis, the media exposure of Italian nurses increased. The aim of this research was to investigate whether and how, during the pandemic, citizens' perceptions of nurses have changed, and if this change were related to the public image of health professionals provided by the mass media. Method: A multi-centric quantitative exploratory study has been conducted. 2114 online questionnaires were analysed for residents of Italy, including health working but excluding the nurses themselves. The results obtained were compared with the results of the scientific literature. Results: Positive perceptions on the part of the citizens towards the nurses are evident, coming to define them "heroes", while discriminatory attitudes are rare. According to the participants, the mass media have conveyed a positive image of the nurses and in relation to this, a percentage of respondents have changed their opinion favourably regarding nurses. Conclusions: The Covid19-related health emergency has helped raise awareness of the nursing role among both citizens and other health workers, even if a lack of knowledge has been highlighted in the training and care role of nurses. The opportunity should be taken by nurses to make well-know their role, promoting public communication, in order to make their image clearer and more truthful.